Effects of coffee components on muscle glycogen recovery: A systematic review - Monteiro Rodrigues Loureiro, L.; Goncalves Reis, C. E.; Macedo da Costa, T. H. (International Journal of Sport Nutrition and Exercise Metabolism, 2018)
Coffee is one of the most consumed beverages in the world, and it can improve insulin sensitivity, stimulating glucose uptake in skeletal muscle when adequate carbohydrate intake is observed. The aim of this review is to analyze the effects of coffee and coffee components on muscle glycogen metabolism. A literature search was conducted according to Preferred Reporting Items for Systematic Reviews and Meta-Analysis, and seven studies were included, that explored the effects of coffee components on various substances and signaling proteins. In one of the studies with humans, caffeine was shown to increase glucose levels, Ca2+/calmodulin-dependent protein kinase phosphorylation, glycogen resynthesis rates, and glycogen accumulation after exercise. After intravenous injection of caffeine in rats, caffeine increased adenosine monophosphate-activated protein kinase (AMPK) and acetyl-CoA carboxylase (ACC) phosphorylation, and glucose transport. In in vitro studies, caffeine raised AMPK and ACC phosphorylation, increasing glucose transport activity and reducing energy status in rat muscle cells. Cafestol and caffeic acid increased insulin secretion in rat beta cells and glucose uptake into human muscle cells. Caffeic acid also increased AMPK and ACC phosphorylation, reducing the energy status and increasing glucose uptake in rat muscle cells. Chlorogenic acid did not show any positive or negative effect. The findings from this review must be taken with caution due to the limited number of studies on the subject. In conclusion, various coffee components had a neutral or positive role in the metabolism of glucose and muscle glycogen, whereas no detrimental effect was described. Coffee beverages should be tested as an option for athletes` glycogen recovery.